2017
DOI: 10.1038/jp.2016.260
|View full text |Cite
|
Sign up to set email alerts
|

Is the Bishop-score significant in predicting the success of labor induction in multiparous women?

Abstract: Labor induction in multiparous women is safe and successful regardless of the initial Bishop-score. In multiparous women the Bishop-score is not a good predictor for the success of labor induction, nor is it a predictor for maternal of neonatal adverse outcomes and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In line with these findings, Navve et al (28) reported that BS is not a good predictor for IOL success, nor is it a predictor for maternal or neonatal adverse outcomes and complications. Recently, Al-Adwy et al (36) found posterior cervical angle of >99.5° yielded the best accuracy in predicting successful IOL compared with the cervical length and Bishop score.…”
Section: Discussion:-supporting
confidence: 59%
See 2 more Smart Citations
“…In line with these findings, Navve et al (28) reported that BS is not a good predictor for IOL success, nor is it a predictor for maternal or neonatal adverse outcomes and complications. Recently, Al-Adwy et al (36) found posterior cervical angle of >99.5° yielded the best accuracy in predicting successful IOL compared with the cervical length and Bishop score.…”
Section: Discussion:-supporting
confidence: 59%
“…Also, Burgos et al (27) reported that in comparison to spontaneous onset of labor, IOL using either misoprostol or oxytocin in breech presentation at term is a reasonable and effective option and was not associated with increased perinatal morbidity or CS rates. Moreover, Navve et al (28) reported non-significant difference regarding IOL outcomes using oxytocin, vaginal prostaglandin E2 insert or a transcervical double balloon catheter and Kawakita et al (29) also reported that in women with oligohydramnios and an unfavorable cervix, misoprostol IOL was comparable to prostaglandin E2 IOL. Moreover, concerning cost/effectiveness of misoprostol IOL, Bierut et al (30) documented that IOL with use MVI generated savings from a hospital perspective in most countries and scenarios, in comparison to alternative technologies.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The statistically significant association of failed IOL and unfavorable Bishop Score is plausible as an unfavorable Bishop score is a sign of non-effaced cervix that may result in failure to achieve first stage of labor. However, the study done at Meir Hospital in Israel showed that there was no association between success of induction and pre-induction Bishop score ≤ 5 [29]. This difference could be due to the fact that the study participants were only multiparous women whose cervices efface easily but, in our study, both nulliparous and multiparous women were included.…”
Section: Discussionmentioning
confidence: 76%
“…The Bishop Scores of >3 has been associated with increased proportion of vaginal birth in some studies 34,35 . Other studies have reported no difference in the proportion of vaginal birth among patients with Bishop Scores of <3 and >3 36,37 . In this study, low proportion of vaginal birth was observed in a group of patients with Bishop Score of >3.…”
Section: Discussionmentioning
confidence: 84%